Infografía digital : La visualización sintética - Valero Sáncho, José Luis (Comunicación (Bosch), 2012)
The aim of this volume is to provide an introduction and selective overview of the rapidly emerging field of computational economics. Computational economics provides an important set of tools that an increasing number of economists will need to acquire in order to understand and do state-of-the-art research in virtually all areas of economics. Articles in the volume range from very applied, policy oriented applications of computational methods, to highly theoretical and mathematically complex analyses of algorithms and numerical methods